PERKELAHIAN ANTAR DESA DI KABUPATEN SERAM BAGIAN TIMUR (KAJIAN PSIKOLOGI HUKUM PIDANA) - Rumadan, Ismail; Muher, Abdul; Rumadan, Salmiwati (TAHKIM, 2023)
The fights that took place in East Seram District generally started with personal issues and then involved the village community, and the consolidation of power started with the younger generation. The factor that prompted the fight to occur came from a historical background with the motto of defending the identity of the country and self-identity. In addition there are other factors such as grudges, herd loyalty, group cohesiveness and others. The fights arose due to the strong psychological influence of the community, so that from a legal perspective, the fights were unlawful acts, from the psychological aspect of criminal law, fighting was a wrong act according to criminal law. Because fighting sacrifices people's property and abuses other people. and for the perpetrators of the fight must be legally processed.Keywords: fighting, between villages, legal psychology